Effects of reflective processes on social-emotional trait development in adulthood: insights from two multi-method studies - Küchler, Gabriela; Borgdorf, Kira Skirwitt Ann; Aguilar-Raab, Corina; Wrzus, Cornelia (Journal of personality, 2026)
Objective This research investigates how reflective processes, such as past-temporal and social comparisons, enhance changes in explicit and implicit self-concepts of social-emotional traits and whether these effects differ with age. Method We conducted two preregistered multi-method studies to examine whether past-temporal or social comparisons predict changes in emotional stability and extraversion. In the longitudinal study (N = 615, aged 18-84 years), we assessed the frequency of past-temporal and social comparisons, explicit and implicit self-concepts of emotional stability and extraversion at two measuring points 6 months apart. In the experimental study (N = 231, aged 18-93 years), we elicited trait-relevant behavioral changes, manipulated past-temporal versus social comparisons, and assessed explicit and implicit trait self-concepts before and after the manipulation. Results Past-temporal and social comparisons predicted longitudinal changes in the explicit self-concept of emotional stability but not extraversion. The experimental study indicated changes in explicit self-concepts of both traits, regardless of the type of comparison standard. Neither type of comparison predicted changes in implicit self-concepts. The findings were generalizable across age groups. Conclusions This research provides the first evidence that comparisons facilitate the change of explicit but not implicit trait self-concepts. We discuss short-term mechanisms of personality development and future directions for examining them experimentally.